Chronic follow-up from the pilot study of a novel substernal extravascular implantable cardioverter-defibrillator. (25th November 2020) - Kotschet, E; Crozier, I; Haqqani, H; Alison, J; Thompson, A; Portway, B; Sawchuk, R; Sherfesee, L; Liang, S; Lentz, L; Degroot, P; O'Donnell, D
Abstract: Background: The investigational Extravascular Implantable Cardioverter Defibrillator (EV ICD) is an implantable defibrillator with defibrillation and pacing therapies, including the potential for antitachycardia pacing (ATP). Purpose: To characterize chronic EV ICD system performance through 12 months of follow-up. Methods: The first-in-human EV ICD Pilot study was prospectively conducted at four centers in Australia and New Zealand. Patients with Class I or IIa indications for ICD were enrolled between July and December of 2018. A defibrillation lead was inserted into the substernal space under radiologic guidance and a device was positioned close to the left midaxillary line. Figure 1 illustrates the implanted EV ICD. Defibrillation testing was conducted at implant and chronically in 5 patients. Follow-ups were conducted at pre-hospital discharge, 2 weeks, 4–6 weeks and 3 months post-implant, and every 6 months thereafter. Results: A total of 26 patients were enrolled and 21 underwent the EV ICD implant procedure with no intraprocedural complications. Median energy for defibrillation at implant was 15 J; mean R-wave amplitude was 3.4±2.0 mV; mean pacing capture threshold was 5.1±2.0 volts. Seventeen of 21 implanted patients entered into chronic follow-up after successful system placement and implant testing, and 14 patients continue to be followed, representing >180 patient-months of total follow-up. Multiple episodes of spontaneous ventricular tachycardia (VT) were detected in one patient and either self-terminated or successfully cardioverted following unsuccessful ATP. One patient received an inappropriate shock secondary to lead tip displacement with subsequent P-wave oversensing. Elective chronic defibrillation testing was performed at physician discretion and converted 5 of 5 patients with ≤40 J (maximum energy of device). Three patients had the system electively removed due to 1) inappropriate shock after lead displacement, 2) recurrent VT without ATP termination, and 3) inadequate chronic safety margin for defibrillation. Conclusions: The EV ICD is a novel platform for delivering high voltage therapy. Chronic system performance has generally remained stable during 12 months of follow-up and the device has demonstrated the ability to detect and treat VT. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Medtronic plc